2014
DOI: 10.1186/s40529-014-0076-0
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil variation in wild populations of Artemisia saharae (Asteraceae) from Tunisia: chemical composition, antibacterial and antioxidant properties

Abstract: BackgroundArtemisia saharae Pomel is a new taxon of Artemisia herba-alba Asso (Asteraceae) which is endemic to Tunisia and Algeria. This shrub, commonly known as white wormwood or desert wormwood, is largely used in folk medicine and as a culinary herb. The bulks aromatic plants come from wild populations whose essential oils compositions as well as their biological properties are severely affected by several factors such as geographic conditions. Therefore, the aim of the present work is to provide more infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…A number of various factors, including genetics, soil, geographic, and climatic conditions affect the essential oil content [40]. In addition, some factors like altitude have been reported to affect the essential oil content [33,40,41]. In our study, the highest content was found in the essential oil from Behbahan population growing at the lowest altitude (394 m), followed by that from Kahnoyeh and Dehdasht populations located at 758 and 971 m a.s.l., respectively.…”
Section: Essential Oil Contentmentioning
confidence: 47%
See 1 more Smart Citation
“…A number of various factors, including genetics, soil, geographic, and climatic conditions affect the essential oil content [40]. In addition, some factors like altitude have been reported to affect the essential oil content [33,40,41]. In our study, the highest content was found in the essential oil from Behbahan population growing at the lowest altitude (394 m), followed by that from Kahnoyeh and Dehdasht populations located at 758 and 971 m a.s.l., respectively.…”
Section: Essential Oil Contentmentioning
confidence: 47%
“…The essential oil content of Behbahan population, with 8.52%, showed a remarkable difference compared to those previously reported for several O. decumbens populations [2,15,18,30,38,39]. A number of various factors, including genetics, soil, geographic, and climatic conditions affect the essential oil content [40]. In addition, some factors like altitude have been reported to affect the essential oil content [33,40,41].…”
Section: Essential Oil Contentmentioning
confidence: 71%
“…Moreover, Thymus praecox growing in higher altitudes have lower essential oil than plants grown in lower altitudes (Avci 2011). While, Zouari et al (2014) in Artemisia saharae (Asteraceae), observed that populations of higher altitudes had the highest amount of essential oil. Sefidkon et al (2002) studied the essential oil compositions of aerial parts of N. fissa collected from Tehran Province, Iran.…”
Section: Discussionmentioning
confidence: 99%
“…The oil is very heterogeneous mixture of many compounds at various concentrations (Zouari et al 2014). Factors such as climatic, and geographic conditions, as well as ontogeny of collected plants can affect formation of essential oil, its composition and its biological activities.…”
Section: Introductionmentioning
confidence: 99%